SETTLEMENT OF MEDICAL DISPUTES AFTER LAW NO. 17 OF 2023 CONCERNING HEALTH - Awangga, Arif (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
Law Number 17 of 2023 revokes 11 previously applicable laws. The dozens of revoked laws are integrated into the Health Law. Law Number 17 of 2023 provides protection for medical and health personnel who practice according to procedures. Law Number 17 of 2023 also regulates the mechanism for enforcing discipline for medical and health personnel and resolving disputes. However, with the issuance of Law Number 17 of 2023 concerning Health, there are several significant changes in the resolution of medical disputes. This law carries a more comprehensive paradigm of health law reform, including simplifying regulations and increasing protection for medical personnel and patients. The research method used is normative legal research/normative juridical legal research. The results of the study show that medical dispute resolution in Indonesia has undergone a significant transformation with the enactment of Health Law Number 17 of 2023 and the implementation of PP 28 of 2024. Both regulations introduce a mediation mechanism as a mandatory initial step in dispute resolution, with the aim of creating a more efficient and transparent process and the advantages of non-litigation dispute resolution are that the process is faster, cheaper, and more flexible. The parties can arrange the dispute resolution process themselves according to their needs and interests.